A novel assay to measure B cell responses to keyhole limpet haemocyanin vaccination in healthy volunteers and subjects with systemic lupus erythematosus - Ferbas, John; Belouski, Shelley S.; Horner, Michelle; Kaliyaperumal, Arunan; Chen, Li; Boyce, Malcolm; Colaço, C. Bernie; McHugh, Neil; Quick, Vanessa; Nicholl, Richard J.; Siu, Gerald; Chung, James (British journal of clinical pharmacology, 2013)
The aim of the study was to characterize performance of a complementary set of assays to measure antigen‐specific immune responses in subjects immunized with a neoantigen. Healthy volunteers (HV) (n = 8) and patients with systemic lupus erythematosus (SLE) (n = 6) were immunized with keyhole limpet haemocyanin (KLH) on days 1 and 29. Serum antibodies were detected using a flow cytometric bead array (CBA) that multiplexed the KLH response alongside pre‐existing anti‐tetanus antibodies. Peripheral blood mononuclear cells were studied by B cell ELISPOT. These assays were built upon precedent assay development in cynomolgus monkeys, which pointed towards their utility in humans. Primary anti‐KLH IgG responses rose to a mean of 65–93‐fold above baseline for HV and SLE patients, respectively, and secondary responses rose to a mean of 260‐170‐fold above baseline. High levels of anti‐tetanus IgG were detected in pre‐immunization samples and their levels did not change over the course of study. Anti‐KLH IgG1‐4 subclasses were characterized by a predominant IgG1 response, with no significant differences in subclass magnitude or distribution between HV and SLE subjects. Anti‐KLH IgM levels were detectable, although the overall response was lower. IgM was not detected in two SLE subjects whodid generate an IgG response. All subjects responded to KLH by B cell ELISPOT, with no significant differences observed between HV and SLE subjects. The CBA and B cell ELISPOT assays reliably measured anti‐KLH B cell responses, supporting use of this approach and these assays to assess the pharmacodynamic and potential safety impact of marketed/investigational immune‐therapeutics.